2000
DOI: 10.1038/emm.2000.14
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and expression of the p27KIP1 and p57KIP2 genes in human gastric cancer

Abstract: Cyclin-dependent kinase inhibitors (CDKI) are negative regulators of cell cycle progression by binding the cyclin-CDK complex and inhibiting the CDK activity. Genetic alteration in the CDKI genes has been implicated for carcinogenesis. To test the genetic alteration in the p27 and p57 genes, KIP family CDKI genes, 30 gastric tumor-normal pairs and 8 gastric cancer cell lines were analyzed for mutations by polymerase chain reaction-single strand conformational polymorphism (PCR-SSCP). No mutation was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…7 Taken together, these observations suggest that that p57 Kip2 exerts tissue-specific effects during development. Interestingly during adulthood, it has also been reported that p57 Kip2 expression is reduced in various tumors, [8][9][10][11][12][20][21][22][23][24] suggesting a possible function for this protein in tumorigenesis. Importantly, decreased p57 Kip2 expression may provide an important prognostic implication for patients with ovarian, hepatocellular and colorectal cancers, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Taken together, these observations suggest that that p57 Kip2 exerts tissue-specific effects during development. Interestingly during adulthood, it has also been reported that p57 Kip2 expression is reduced in various tumors, [8][9][10][11][12][20][21][22][23][24] suggesting a possible function for this protein in tumorigenesis. Importantly, decreased p57 Kip2 expression may provide an important prognostic implication for patients with ovarian, hepatocellular and colorectal cancers, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]23 In spite of frequent low/absence of p57 Kip2 expression in various tumors, rare/no somatic mutations of p57 Kip2 gene are found in these tumors. [8][9][10][11][12] These observations suggest that inactivation of p57 Kip2 gene expression, rather than mutations in the p57 Kip2 gene, accounts for the involvement of p57 Kip2 in other types of cancer. Accordingly, inactivation of p57 Kip2 by regional promoter hypermethylation and histone deacetylation has been suggested in human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Shin and colleagues in 2000 (125), neither mutations of the CDKN1C gene (30 samples) nor its reduced expression in gastric cancer cell lines were reported. Conversely, p57 Kip2 immunoblotting analysis in gastric cancer specimens showed lower levels of the protein (in 36 patients) compared with normal counterparts (126).…”
Section: P57 Kip2 Content In Human Malignanciesmentioning
confidence: 99%
“…Histone acetylation status is regulated by the opposing actions of histone acetyl-transferases (HATs) and histone deacetylases (HDACs) (Smith and Denu, 2009). During the last years HDAC-inhibitors have become one of the most promising classes of chemotherapeutics with profound antitumour effects (Glaser, 2007), and are successfully used to inhibit cell growth of lots of carcinoma cells in vitro (McBain et al, 1997;Shin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%